Anterior cingulate cortex connectivity is associated with suppression of behaviour in a rat model of chronic pain. (June 2018) - Morris, Laurel S.; Sprenger, Christian; Koda, Ken; de la Mora, Daniela M.; Yamada, Tomomi; Mano, Hiroaki; Kashiwagi, Yuto; Yoshioka, Yoshichika; Morioka, Yasuhide; Seymour, Ben
A cardinal feature of persistent pain that follows injury is a general suppression of behaviour, in which motivation is inhibited in a way that promotes energy conservation and recuperation. Across species, the anterior cingulate cortex is associated with the motivational aspects of phasic pain, but whether it mediates motivational functions in persistent pain is less clear. Using burrowing behaviour as an marker of non-specific motivated behaviour in rodents, we studied the suppression of burrowing following painful confirmatory factor analysis or control injection into the right knee joint of 30 rats (14 with pain) and examined associated neural connectivity with ultra-high-field resting state functional magnetic resonance imaging. We found that connectivity between anterior cingulate cortex and subcortical structures including hypothalamic/preoptic nuclei and the bed nucleus of the stria terminalis correlated with the reduction in burrowing behaviour observed following the pain manipulation. In summary, the findings implicate anterior cingulate cortex connectivity as a correlate of the motivational aspect of persistent pain in rodents.